Evidence Based Clinical Study on Alopecia (Advancements in Homeopathic Research, 2022)
A total of 100 well diagnosed cases of ALOPECIA Areata & TOTALIS were registered for treatment at Geetanjali Homoeopathic Clinic & Research Center Lucknow from October 2008 to November 2015. Clinical diagnosis followed by constitutional treatment with homoeopathic medicines showed encouraging results in majority of cases. Out of 100 cases 21 cases showed complete re-growth of all the lost patches of hair in both alopecia totalis and areata both taken together. While 42 cases showed improvement in few patches and rest 25 cases did not show any response to the treatment, whereas 12 cases worsened after treatment in which increase in size and number of bald patches was observed. Duration of treatment varied from case to case depending on the size and number of the bald patches and response of the patient. In depth case taking was done in each and every case on holistic principle giving more emphasis on causation and mental symptoms. The outcome of this study is very encouraging, which gives new dimensions and confidence to young Homoeopaths in treatment of alopecia aerata/totalis strictly abiding by Hahnemaanian principles of minimum dose and minimum repetition.
Keywords: ALOPECIA; Homoeopathic; treatment